Power flow optimization in a microgrid with two kinds of energy storage. Issue 3 (3rd May 2016) - Rigo-Mariani, R.; Roccuzzo, V.; Sareni, B.; Repetto, M.; Robaum, X.
Abstract : Purpose: – The purpose of this paper is to present the optimization of the power flows inside a microgrid with renewable sources and two kinds of storage. The considered microgrid consists in commercial buildings with maximum daily peak value of 50 kW, photovoltaic arrays with total capacity of 175 kW, a 50 kW/50 kWh high speed flywheel storage and a 50 kW/50 kWh set of Li-ion accumulators. Design/methodology/approach: – The power flows in the microgrid are optimized the day ahead at one hour discretization in order to minimize the electric bill. Several scheduling strategies are proposed for solving the corresponding optimization problem including standard deterministic methods, stochastic algorithms and hybrid heuristics. Findings: – All scheduling strategies investigated in the paper are compared with regard to their accuracy and computational time. Originality/value: – Beyond the comparison of different algorithms devoted to the power flow optimization problem, the authors approach also addresses the integration of battery ageing in the scheduling strategy.